1987
DOI: 10.1111/j.1540-8191.1987.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Sinus Interventions: From Concept to Clinics

Abstract: For almost 100 years the coronary venous system has attracted researchers as an access route to deprived myocardium. Different concepts have been tried and numerous experimental studies have been performed to evaluate whether coronary sinus occlusion, retroinfusion, and retroperfusion of arterial blood via the coronary sinus represent an effective treatment of myocardial ischemia. The early successful studies of Drs. Gregg, Eckstein, Beck and others led to the application of the Beck II procedure, a permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…(2)) fitted to the envelopes of venous pressure is designed such that a plateau is reached assymptotically for sufficiently long coronary sinus occlusion times (Schreiner et al, 1987). The height of the plateau can be calculated analytically from the regression coefficients of the fitted function: Downloaded by [University of Arizona] at 07:12 03 February 2015 It has been suggested that the height of the plateau of coronary venous pressure is the essential parameter that provides the hemodynamic impetus for retrograde flow and upon which the automatic control of coronary sinus interventions could be based (Mohl, 1987(Mohl, , 1988. In light of its importance, Fig.…”
Section: Rise Of Venous Pressure With Different Srp Flow Ratesmentioning
confidence: 99%
“…(2)) fitted to the envelopes of venous pressure is designed such that a plateau is reached assymptotically for sufficiently long coronary sinus occlusion times (Schreiner et al, 1987). The height of the plateau can be calculated analytically from the regression coefficients of the fitted function: Downloaded by [University of Arizona] at 07:12 03 February 2015 It has been suggested that the height of the plateau of coronary venous pressure is the essential parameter that provides the hemodynamic impetus for retrograde flow and upon which the automatic control of coronary sinus interventions could be based (Mohl, 1987(Mohl, , 1988. In light of its importance, Fig.…”
Section: Rise Of Venous Pressure With Different Srp Flow Ratesmentioning
confidence: 99%
“…Three main categories of CSI have been described and adopted over the last century: retroperfusion, retroinfusion and coronary sinus occlusion2 (figure 1). Retroperfusion technique aimed to provide arterialised blood to the ischaemic myocardium via the coronary vein system 2.…”
Section: Introductionmentioning
confidence: 99%
“…Retroperfusion technique aimed to provide arterialised blood to the ischaemic myocardium via the coronary vein system 2. Retroinfusion technique aimed to deliver drugs to the myocardium essentially for cardioprotection, by a retrograde approach involving the access to the coronary sinus 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations